Effect of feeding fine maize particles on the reticular pH, milk yield and composition of dairy cows. Issue 3 (4th July 2013) - De, R.; Marchesini, G.; Stefani, A.‐L.; Barberio, A.; Andrighetto, I.; Segato, S.
Summary The particle size of cereal grains has been found to modulate the rate of passage from the rumen and the digestibility of starch and neutral detergent fibre (NDF), but few studies have examined its impact on reticular pH. The study aimed to evaluate the effect of feeding finely ground maize on the risk of ruminal acidosis, milk yield and composition. Twelve Holstein‐Friesian cows were assigned to one of two experimental groups and fed according to a cross‐over design. Diets were isoenergetic and isonitrogenous and were characterised by the same NDF and ADF, differing only in maize particle size. In the control diet (Ct), the maize meal was ground to 1.0 mm, whereas in the experimental diet, it was finely ground (Fg) to 0.5 mm. The pH and temperature of the reticulum were continuously measured in eight cows throughout the trial using indwelling sensors. Dry matter intake was higher in cows offered Fg diet than in Ct (19.0 vs. 20.3 kg/day; p = 0.067). However, milk yield (p = 0.855) and the 3.5% fat‐corrected milk (FCM) (p = 0.724) did not show any differences between the diets. Casein (2.48 vs. 2.57%; p = 0.035) and crude protein (CP) (3.18 vs. 3.31%; p = 0.021) resulted higher in Fg. Similarly, starch digestibility increased in animals offered Fg diet versus Ct (0.94 vs. 0.98; p = 0.078). Among the reticular parameters, the Fg‐fed cows spent a significantly higher time below the 5.5 pH threshold (15 vs. 61 min/day; p = 0.047) and had an average daily variation in reticular pH characterised by a lower nadir pH (5.95 vs. 5.72; p < 0.001) and a higher pH range (0.79 vs. 0.94; p = 0.003). In this study, grain particle size affected the risk of the onset of ruminal acidosis. Therefore, it should be carefully considered when formulating rations.